2012
DOI: 10.1042/bj20111268
|View full text |Cite
|
Sign up to set email alerts
|

EHD2 shuttles to the nucleus and represses transcription

Abstract: EHD {EH [Eps15 (epidermal growth factor receptor substrate 15) homology]-domain-containing} proteins participate in several endocytic events, such as the internalization and the recycling processes. There are four EHD proteins in mammalian cells, EHD1–EHD4, each with diverse roles in the recycling pathway of endocytosis. EHD2 is a plasma-membrane-associated member of the EHD family that regulates internalization. Since several endocytic proteins have been shown to undergo nucleocytoplasmic shuttling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…This is an important question because a stabilized repressor may increase the chromatin resident time of its associated chromatin modifiers. In some cases, temporal control of stability is achieved by mechanisms that shuttle the repressors between the nucleus and cytoplasm (29)(30)(31). Although REST has been observed in some cellular contexts in the cytoplasm (28,31,32), its half-life in this cell compartment has not been measured, and whether its cytoplasmic complexes contain kinases or phosphatases has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important question because a stabilized repressor may increase the chromatin resident time of its associated chromatin modifiers. In some cases, temporal control of stability is achieved by mechanisms that shuttle the repressors between the nucleus and cytoplasm (29)(30)(31). Although REST has been observed in some cellular contexts in the cytoplasm (28,31,32), its half-life in this cell compartment has not been measured, and whether its cytoplasmic complexes contain kinases or phosphatases has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Entry of EHD2 into the nucleus depends on a nuclear localization sequence (NLS) present in its helical domain. We also showed that its exit from the nucleus depends mainly on its SUMOylation (SUMO-small ubiquitin like modifier) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, this posttranslational modification changes the surface of a target protein, enabling/disabling interactions with other proteins [ 32 ]. Although a number of endocytic proteins have been shown to undergo SUMOylation, EHD2 is the only EHD member shown to be modified by SUMOylation [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…and thus fail to insert properly into the plasma membrane. We rationalize that under such conditions where membrane binding is partially impaired, the lysine residues in the EHD2 helical domain, which act both as membrane contact sites [ 9 ] and a bipartite nuclear localization sequence [ 27 ], are now free to act in the latter capacity and promote EHD2 transport to the nucleus. Indeed, EHD2 has been described as a transcriptional repressor [ 27 ].…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, despite normal dimerization and binding, EHD2 NPF-to-APA displayed a dramatic relocation to the nucleus ( Fig 3D ). Although EHD2 has a bipartite nuclear localization sequence and many cells display a portion of their EHD2 in the nucleus ( Fig 3C ) [ 27 ], the NPF-to-APA mutant displayed a primarily nuclear localization ( Fig 3D ). Accordingly, despite the yeast two-hybrid binding, we were unable to detect EHD2 NPF-to-APA interactions with Syndapin2 by co-immunoprecipitation, likely due to the mutant’s mislocalization exclusively to the nucleus ( S2 Fig and S1 Table ).…”
Section: Resultsmentioning
confidence: 99%